Estimation of genetic diversity and relationship among goats of Maharashtra state - MISHRA, PRIYANKA; DIXIT, S P; AGGARWAL, R A K; BEHL, JYOTSNA; DANGI, P S; VERMA, N K (The Indian Journal of Animal Sciences, 2017)
Sangamneri, Osmanabadi, Berari and Konkan Kanyal are the known breeds of Maharashtra state of India. DNA from 50 unrelated goats of each breed was analysed to know the genetic diversity using 25 microsatellite markers. A total of 479 alleles (192 in Sangamneri, 153 in Osmanabadi, 294 in Berari and 255 in Konkan Kanyal) were observed. Mean number of alleles per locus and observed heterozygosity were 7.68, 6.12, 11.76, 10.20 and 0.53, 0.42, 0.67 and 0.58 for Sangamneri, Osmanabadi, Berari and Kanyal goat populations respectively. The fixation coefficients of sub-populations within the total population (FST), varied from 0.04 (OarHH64) to 0.68 (OarJMP29) with a mean of 0.17. The L-shaped mode-shift curve indicated the absence of reduction in effective population size. The genetic distances between four breeds indicated the distinctness of Berari and Konkan Kanyal from Sangamneri and Osmanabadi. Berari and Konkan Kanyal although exists at different geographic locations but show some genetic overlapping. The Nei's genetic distance observed between breeds were 0.472 (Sangamneri and Osmanabadi), 0.667 (Sangamneri and Berari), 0.819 (Sangamneri and Konkan Kanyal), 0.797(Osmanabadi and Berari), 0.994 (Osmanabadi and Konkan Kanyal) and 0.092 (Berari and Konkan Kanyal). Konkan Kanyal is genetically more distant from Osmanabadi and Sangamneri than Berari. Sangamneri and Osmanabadi goat breeds were assigned to cluster-3 where the proportion of membership for each breed was 0.975 (Sangamneri) and 0.992 (Osmanabadi). Kanyal and Berari goat populations were assigned to another cluster (Cluster 4). The proportion for their membership was 0.923 (Konkan Kanyal) and 0.869 (Berari).